Mae Jemison : the first African American woman in space - Alagna, Magdalena (New York, NY : Rosen Central, 2004)
Provides insights into the life of Mae Jemison, the first female African American astronaut, including some of the steps she took to reach her goals.
Includes bibliographical references (p. [107-108] and index.
Keywords: Jemison, Mae, -- 1956- -- Juvenile literature; Jemison, Mae, -- 1956-; African American women astronauts -- Biography -- Juvenile literature; Astronauts -- United States -- Biography -- Juvenile literature; Astronauts; African Americans -- Biography; Women -- Biography